The vitamin D receptor agonist EB1089 can exert its antiviral activity independently of the vitamin D receptor. - Janejira Jaratsittisin; Wannapa Sornjai; Thanathom Chailangkarn; Anan Jongkaewwattana; Duncan R Smith (PLoS ONE, 2023)
Vitamin D has been shown to have antiviral activity in a number of different systems. However, few studies have investigated whether the antiviral activity is exerted through the vitamin D receptor (VDR). In this study, we investigated whether the antiviral activity of a vitamin D receptor agonist (EB1089) towards dengue virus (DENV) was modulated by VDR. To undertake this, VDR was successively overexpressed, knocked down and retargeted through mutation of the nuclear localization signal. In no case was an effect seen on the level of the antiviral activity induced by EB1089, strongly indicating that the antiviral activity of EB1089 is not exerted through VDR. To further explore the antiviral activity of EB1089 in a more biologically relevant system, human neural progenitor cells were differentiated from induced pluripotent stem cells, and infected with Zika virus (ZIKV). EB1089 exerted a significant antiviral effect, reducing virus titers by some 2Log10. In support of the results seen with DENV, no expression of VDR at the protein level was observed. Collectively, these results show that the vitamin D receptor agonist EB1089 exerts its antiviral activity independently of VDR.